Laju Keausan dan Kekerasan Kampas Rem Pada Sistem Pengereman Sepeda Motor - Richard A M Napitupulu; Charles S.P Manurung; Chossi Sembiring (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2022)
The braking system is a very important mechanism on the vehicle as a safety tool and ensures a safe vehicle. One of the most important parts of the braking mechanism is the brake lining. The influence of material selection, working conditions in the braking process can affect the wear of the brake lining, which has an impact on the life of the brake lining and the hardness of the brake lining. This study varies the working pressure of the braking process from 5, 10 and 15 psi, and compares 8 types of aftermarket brake lining samples with genuine part brake linings. And the results show that in this case it is known that the average hardness of non-genuine aftermarket brake wear is lower than that of aftermarket genuine ones and the wear rate of non-genuine brake lining materials is lower.